Assessment of Occupational Hazards in Healthcare Facilities in Benghazi, Libya- 2024: A Cross-Sectional Study - B. Yousif , Amenh; Abuzreda , Abdelsalam; E. Aleawami , Muhamad; A. Albrouni, Ayoub; K. Alamami , Hamed; G. Elmesmary, Atia; G. Elmesmary, Atia (Libyan Journal of Public Health Practices, 2026)
Healthcare workers are constantly exposed to a variety of occupational hazards, including biological, chemical, and physical hazards, which can compromise their health and safety. Understanding the extent of these hazards is crucial for improving working conditions and strengthening preventive measures within healthcare facilities. A cross-sectional study was conducted to evaluate occupational risk exposures and associated health outcomes among 253 healthcare workers (HCWs) from five healthcare facilities in Benghazi, Libya, over four months. Data were collected via structured questionnaires and analyzed using bivariate and multivariate methods, with statistical significance set at p < 0.05. Findings revealed a high prevalence of psychological distress (62.8%), musculoskeletal disorders (61.3%), and biological exposures (55.7%), alongside a significant gap between risk awareness (73.1%) and formal training (46.6%). Multivariate analysis identified a lack of safety training as a significant independent predictor for multiple adverse outcomes: musculoskeletal disorders (a OR=1.85), work absenteeism (a OR=2.18), and accidental exposure to biological materials (a OR=2.85). Work absenteeism was also associated with psychological distress (a OR=3.05), and accidental biological exposure was strongly linked to inconsistent glove use (a OR=4.25). The results underscore the urgent need for ergonomic interventions, mental health support, and, most critically, comprehensive safety training to protect healthcare workers in Benghazi.